UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS XII IPS-1 PADA MATERI TEKS DISCUSSION PELAJARAN BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN FOCUS GROUP DISCUSSION DI SMA NEGERI 1 KEMBANG TANJONG KABUPATEN PIDIE - Yusmadaniar Yusmadaniar (Jurnal Real Riset, 2022)
This study aims to examine the effectiveness of the Focus Group Discussion Method on increasing students' learning motivation in the field of English studies. The subjects of this study were class XII students for the academic year 2020-2021. There are 25 students, consisting of 13 male students and 12 female students. This research took place in two cycles, each cycle consisted of; “planning, action, observation and reflection. The data collected in this study include: student learning outcomes, observations of activities during learning, post-test results given and reflections from reflection quiz sheets. Observation of teacher performance in learning by using Focus Group Discussion method and reflection from research partners, taken at the end of each cycle. The results of the research in cycles 1 and 2 are 1.) Teacher activity has increased well, namely achieving (standard score "good") has mastered and applied the Focus Group Discussion model in learning and at the end of cycle 2 in general it has been around (standard score" is very good). 2.) Student participation during KBM at the first meeting of cycle 1 was still low (ranging from the standard of "fair"), but at the second meeting of cycle one it began to increase (standard score was "good") and the class atmosphere became more harmonious. At the end of cycle 2 in general, students had partitioned “very well” at the time of the KMB. 3.) Student learning outcomes at the end of Cycle 1 increased to 16 of 25 students (64%) who achieved the standard value of learning completeness compared to before the CAR took place of 25 students, 15 (60%) students who completed. At the end of cycle 2, it was getting better, reaching 20 out of 24 students (80%) achieving the standard of mastery learning, their average score was above the KKM: 68. Based on the results of this study, it can be concluded that the application of Focus Group Discussion learning has been proven to improve teacher professionalism, participation and student learning outcomes in class XII IPS-1 SMA Kembang Tanjong on the subject matter of "Text Discussion".Keywords: Learning Outcomes, Learning Model Focus Group Discussion